ERRATUM - Kim, Karam; Yu, Jungho (Journal of Civil Engineering and Management, 2016)
Erratum on the article 'A process to divide curved walls in IFC-BIM into segmented straight walls for building energy. Journal of Civil Engineering & Management, 22(3), p. 456.First published online: 15 Dec 2015